Characterization and taste masking evaluation of microparticles with cetirizine dihydrochloride and methacrylate-based copolymer obtained by spray drying - Amelian Aleksandra; Szekalska Marta; Ciosek Patrycja; Basa Anna; Winnicka Katarzyna (Acta Pharmaceutica)
Taste of a pharmaceutical formulation is an important parameter for the effectiveness of pharmacotherapy. Cetirizine dihydrochloride (CET) is a second-generation antihistamine that is commonly administered in allergy treatment. CET is characterized by extremely bitter taste and it is a great challenge to successfully mask its taste; therefore the goal of this work was to formulate and characterize the microparticles obtained by the spray drying method with CET and poly(butyl methacrylate-co-(2-dimethylaminoethyl) methacrylate-co-methyl methacrylate 1:2:1 copolymer (Eudragit E PO) as a barrier coating. Assessment of taste masking by the electronic tongue has revealed that designed formulations created an effective taste masking barrier. Taste masking effect was also confirmed by the in vivo model and the in vitro release profile of CET. Obtained data have shown that microparticles with a drug/polymer ratio (0.5:1) are promising CET carriers with efficient taste masking potential and might be further used in designing orodispersible dosage forms with CET.